Size does matter: An exploration of the relationship between licensed venue capacity and on‐premise assaults. (22nd June 2021) - Miller, Peter; Curtis, Ashlee; Millsteed, Melanie; Harries, Travis; Nepal, Smriti; Walker, Samantha; Chikritzhs, Tanya; Coomber, Kerri
Abstract: Aims: Venue capacity has been proposed as a factor associated with increased number of violent incidents on‐premises, though no specific research has demonstrated this association, and instead has tended to focus on the relationship between crowding and aggression. The aim of current paper is to investigate the association between venue capacity and the number of violent incidents on‐premises. Methods: Venue capacity data (the maximum capacity listed on the liquor license) were obtained for all venues in central Melbourne from 2010 until 2016. These data were then matched with police‐recorded on‐premises assaults that occurred within high‐alcohol hours (Friday and Saturday 8 pm –6 am ) inside the venue. Results: Analyses were conducted on 5729 venue‐years (yearly assault counts per venue, per year) across central Melbourne. Compared with venues that have a maximum capacity of between 0 and 100 patrons, venues with higher capacities have increasingly more recorded assaults. Venues with maximum capacities between 501 and 1000 are 6.1 times more likely to have an assault recorded compared with venues with a maximum capacity between 0 and 100. Further, each additional high‐alcohol hour that a venue can be open for is associated with a 72% increase in the number of recorded assaults. Conclusions: Greater venue capacity was found to be strongly associated with an increased risk of violent incidents for any given venue. This was further exacerbated by late‐night trading which substantially adds to the risk of assaults inside the venue.